Combined effect of compaction and clay content on the mechanical properties of adobe brick. (December 2020) - Dormohamadi, Mansoure; Rahimnia, Reza
Abstract: Iran is one of the oldest countries in the world, benefiting from adobe-based architecture. The present study investigates the effect of dynamic compaction on mechanical properties of adobes using clayey-silty soils from Ardakan city, Yazd, Iran, with a focus on the compressive, tensile and flexural strengths in relation with the particle size distribution of the earth. However, it is found that the results of this mechanical stabilization are in function of the mineralogical compositions as well. In this regard, adobe samples in the control and experimental (compacted) groups were made with six soil types of six different mines, and their physical, mineralogical, and chemical characteristics were determined. Compressive, tensile, and flexural strengths of samples were examined, and the mechanical strength of the unbaked adobe bricks was correlated with the physical properties of the soils. The laboratory studies confirmed the direct relationship between dynamic compaction and mechanical strength. The results showed that soil compaction in the experimental adobes results in an increase of compressive strength by 79.43 %, tensile strength by 42.42 %, and flexural strength by 75.00 % compared to control adobes which lacks compaction. So, dynamic compaction is an acceptable method for manufacturing earthen materials such as adobe according to the required standards.